Norwegian scabies in human immunodeficiency virus and tuberculosis-infected child: A case report - Wijaya, Hendri; Kollins, Fini; Lubis, Inke ND.; Pasaribu, Ayodhia P.; Evalina, Rita; Nababan, Kristo A.; Paramita, Deryne A. (Narra J, 2024)
Norwegian scabies is a rare scabies with the manifestation of thick crusts of the extremities of the skin that contain eggs and mites. Several conditions in which scabies infection is easily transmitted include immunocompromised, home nursing, and severe neurological disorder. The aim of this case report was to present a thorough analysis of a comprehensive resource for the management of Norwegian scabies patients, with a specific focus on individuals who also have HIV or other immunocompromising diseases.  A 1-year-and-7-month-old boy was presented to the hospital with a chief complaint of a thick crust that he had experienced for four months. It began as a red papule in the lower extremity, then crusted and spread to the whole body. The patient kept scratching due to itching, had a recurrent fever and diarrhea for three months, and cough for one month. The patient was diagnosed with human immunodeficiency virus (HIV) and pulmonary tuberculosis at three months, suspected to get the infection from the parents. Sarcoptes scabiei was found from microscopy examination of skin scraping. The patient received holistic treatment, including antiretroviral drugs, antituberculosis medication, scabies treatment, and malnutrition treatment. Appropriate scabies treatment aimed at peeling crusted skin, relieving itching, and increasing the patient ability to use the extremities. Comorbidity conditions caused by HIV and pulmonary tuberculosis should also be treated to optimize the outcome. The patient was discharged in good condition with sanitation education and regular follow-up at the outpatient clinic. This case highlights that Sarcoptes scabiei infestation may be a clue to an immunocompromised condition. Holistic therapy aiming to cure underlying infection, infestation and underlying nutrition and psychosocial problems must be addressed to fully cure this high-burden case.